2014
DOI: 10.1016/j.taap.2014.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aroclor 1260 exposure in a mouse model of diet-induced obesity and non-alcoholic fatty liver disease

Abstract: Polychlorinated biphenyls (PCBs) are persistent organic pollutants associated with non-alcoholic fatty liver disease (NAFLD) in epidemiologic studies. The purpose of this study was to evaluate the hepatic effects of a PCB mixture, Aroclor 1260, whose composition mimics human bioaccumulation patterns, in a mouse model of diet-induced obesity (DIO). Male C57Bl/6J mice were fed control diet or 42% high fat diet (HFD) and exposed to Aroclor 1260 (20 mg/kg or 200 mg/kg in corn oil) for 12 weeks. A glucose tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
128
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(148 citation statements)
references
References 42 publications
14
128
5
1
Order By: Relevance
“…For comparison, we examined the expression of the predominant mouse hepatic Cyp3a11 enzyme in the SS model and found a trend toward lower (20% 6 6%, P = 0.10) mRNA expression levels in mice on a high-fat diet (n = 6) than in those on a normal diet (n = 6). In the context of previous reports, results in mouse models of NAFLD have been heterogeneous with some demonstrating decreased (Yoshinari et al, 2006;Ghose et al, 2011;Wahlang et al, 2014) or induced (Fisher et al, 2008;Spruiell et al, 2014) expression of Cyp3a11. Similarly, rat models of hepatic steatosis are conflicting, with some reporting decreased Cyp3a expression (Leclercq et al, 1998) and others showing higher levels (Ghoneim et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…For comparison, we examined the expression of the predominant mouse hepatic Cyp3a11 enzyme in the SS model and found a trend toward lower (20% 6 6%, P = 0.10) mRNA expression levels in mice on a high-fat diet (n = 6) than in those on a normal diet (n = 6). In the context of previous reports, results in mouse models of NAFLD have been heterogeneous with some demonstrating decreased (Yoshinari et al, 2006;Ghose et al, 2011;Wahlang et al, 2014) or induced (Fisher et al, 2008;Spruiell et al, 2014) expression of Cyp3a11. Similarly, rat models of hepatic steatosis are conflicting, with some reporting decreased Cyp3a expression (Leclercq et al, 1998) and others showing higher levels (Ghoneim et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…Future experimental studies are required to evaluate the possible mechanistic role of PCBs in liver cell death. While animal studies have reported interactions between PCB exposures and diet-induced obesity in steatohepatitis 22,23 , no significant interaction was found between ƩPCBs and BMI on liver disease status in this study. However, this analysis may have been limited by the high prevalence of overweight/obesity and the elevated PCB levels in this population.…”
Section: Associations Between Individual Pcb Congeners and Ck18-indiccontrasting
confidence: 88%
“…Although not directly tested in this study, it is conceivable that PCBs could mediate a transition from NASH to TASH by decreasing apoptosis and promoting more proinflammatory necrotic hepatocyte death. While PCBs were a 'second hit' in the transition from dietinduced steatosis to more advanced liver disease in animal studies 23,[107][108][109] , a significant interaction between PCBs and BMI on liver disease status was not observed in the present study. Perhaps the high rates of overweight/obesity and elevated PCB levels in the cohort limited the ability to detect interactions occurring at lower exposures and body weights.…”
contrasting
confidence: 77%
See 2 more Smart Citations